Community-Based Sanitation Risk Model to Reduce Childhood Diarrhea in Flood-Prone Urban Settlements - Erny Kusdiyah; Ahmad Syauqy; Mirna Marhami Iskandar; Armaidi Darmawan; Wahyu Indah Dewi Aurora; Ratna Sugiarti (Poltekkes Kemenkes Surabaya, 2026)
Childhood diarrhea remains a major public health concern in flood-prone urban settlements, where inadequate sanitation and environmental contamination are common. This study aimed to develop and validate a community-based sanitation risk model to identify key environmental and behavioral factors associated with childhood diarrhea. An analytical cross-sectional design was conducted among 240 households with children under five years of age. Data were collected through structured interviews, household sanitation observations, and environmental assessments, covering variables such as water source, latrine condition, waste disposal, drainage, handwashing practices, and flood exposure. Bivariate analysis was used to assess associations between sanitation variables and diarrhea, followed by multivariable logistic regression to determine independent predictors and construct the risk model. The results showed that The two-week prevalence of childhood diarrhea was 27.5%. Multivariable analysis identified contaminated water sources (AOR = 3.42; 95% CI: 1.95–5.99), clogged or non-functional drainage (AOR = 3.85; 95% CI: 2.12–6.97), improper solid waste disposal (AOR = 2.67; 95% CI: 1.56–4.61), unimproved latrines (AOR = 2.11; 95% CI: 1.25–3.58), and inadequate handwashing behavior (AOR = 2.48; 95% CI: 1.40–4.38) as significant predictors of diarrhea. The model demonstrated good discrimination in identifying high-risk households. In conclusion, the The developed community-based sanitation risk model provides a simple, evidence-based tool for identifying households at high risk of childhood diarrhea in flood-prone urban settlements. This model can support targeted sanitation interventions and strengthen community-level disease prevention programs.